Factors associated with complications in inguinal hernioplasty in a hospital of the armed forces of Peru, 2013-2017 - Flores Agostini, Fernando (2018)
ABSTRACT Objective: To determine the factors associated with complications in inguinal hernioplasty in a hospital of the armed forces of Peru, 2013-2017. Methods: Observational, quantitative, retrospective, analytical type case and control study. There were 52 cases and 104 controls, obtained under the spreadsheet and chosen by simple probabilistic sampling. We analyzed the association measures through the Odds Ratio (OR). A 95% confidence interval (95% CI) was used and the chi-squared statistic was applied with a statistical significance level of less than 0.05. Results: It was found that seroma was the most frequent complication. With regard to sex, an OR was observed: 1.41; 95% CI: 0.655 - 3.05; p 0.375, for age, an OR was obtained: 4.56; 95% CI: 2.24 - 9.28; p 0.00. For obesity, an OR was found: 28.52; 95% CI: 10.9-74.60; 0.00. In the diameter of the hernial ring, OR was obtained: 1.83; 95% CI: 0.76 - 4.39; p 0.17. With respect to the surgical technique, the analysis showed an OR: 2.52; 95% CI: 1.13 - 5.58. Finally, with respect to surgical time, an OR was found: 12.37; 95% CI: 5.23-29.26; p 0.00. Conclusion: It is concluded that there are risk factors associated with complications after inguinal hernioplasty such as age greater than or equal to 65 years, obesity, conventional type surgical technique and operative time equal to or greater than 90 minutes. Key words: Associated factors; Complications; Inguinal hernioplasty. (source: MeSH NLM) DOI:  10.25176/RFMH.v18.n3.1588